Pengaruh Sistem Informasi Manajemen Pendidikan Terhadap Kualitas Pelayanan Administrasi Siswa di SMK Muhammadiyah 3 Terpadu Pekanbaru - Anshori, Ahmad; Susiani, Ani; Ainulyaqin, Nady; Daulay, Mahfuzah Ilma; Fadillah, Rizky (Universitas Cokroaminoto Yogyakarta, 2025)
This study aims to describe the impact of the implementation of the Education Management Information System (EMIS-Pendidikan) on the quality of student administration services at SMK Muhammadiyah 3. Using a descriptive qualitative approach, data were collected through direct observation and interviews with administrative staff and teachers. Data analysis was conducted through data reduction, data presentation, and conclusion drawing to identify MIS usage patterns and their impact on administrative services. The results show that the implementation of MIS, such as e-Raport and Pijar Online, has a positive impact on efficiency, accuracy, transparency, and service satisfaction. Interview data showed an increase in the speed of grade processing, a decrease in input errors, and ease of access to information for students and parents. However, the effectiveness of MIS is still influenced by limitations in digital infrastructure, user technological literacy, and managerial support. Therefore, improving human resource competency and strengthening technological facilities are key to the success of school digital transformation.